2010
DOI: 10.4995/wrs.2005.520
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy study of soluble bacitracin (Bacivet S®) in a chronically infected epizootic rabbit enteropathy environment.

Abstract: ABSTRACT:The present study evaluated under field conditions the efficacy of bacitracin zinc soluble powder (Bacivet S ® ) for the treatment of Epizootic Rabbit Enteropathy (ERE). A blinded study was conducted in compliance with the "Good Clinical Practice" guidance. The trial site was known to be chronically infected with ERE. A total of 384 weaned rabbits (30 days of age) were enrolled in the study. They were randomly distributed over 6 rows of cages located in the same experimental room. Two rows of cages re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…In agreement with previous descriptions of ERE symptoms Maertens et al, 2005;Licois, 2010), no visible inflammation of the walls of the intestinal tract was detected in ERE-affected animals. It was also observed that the distal colon was often empty or just contained mucus.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…In agreement with previous descriptions of ERE symptoms Maertens et al, 2005;Licois, 2010), no visible inflammation of the walls of the intestinal tract was detected in ERE-affected animals. It was also observed that the distal colon was often empty or just contained mucus.…”
Section: Resultssupporting
confidence: 78%
“…Even if this percentage could be in keeping with that (52.9%) found by Maertens et al (2005), the ERE morbidity seems very low. ERE is characterised by spreading very quickly and morbidity can rise to 100% after experimental inoculation .…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations